Sistem Pendukung Keputusan Pemilihan Pondok Pesantren Tahfizhul Qur’An Terbaik Di Malang Menggunakan Metode Analitycal Hierarchy Process Dan Promethee - Eko Teguh Prasetyo; Diah Arifah Prastiningtyas; Meivi Kartikasari (J-INTECH ( Journal of Information and Technology), 2021)
Islamic boarding schools are one of the educational institutions that provide non-formal education in the Islamic religious field. Many Islamic boarding schools carry out Qur'an memorization programs (tahfizhul quran). Memorizing Qur'an is an activity that is very noble in the eyes of Allah SWT, because the Prophet Sallallaahu'alaihi Wasallam said which means "the best of you are those who study the Qur'an and teach it" (Narrated by Al Bukhari 4639). In Malang, there are many tahfizhul Qur'an Islamic boarding schools which have their respective strengths and weaknesses, thus making some people confused in determining where they or their children will study. On the basis of these problems, a system is needed to support decisions in the selection of a Islamic boarding school in Malang using the Analitycal Hierarchy Process (AHP) and Promethee Methods. The purpose of this system is to be able to assist some people in selecting the Islamic boarding schools with the criteria of the education system, education level, facilities, environmental conditions, the reputation of the boarding school, alumni and fees. The AHP method is used to find the weight of the criteria while the Promethee method is used to rank the Islamic boarding schools. After analyzing, designing, implementing and testing the system, it can be concluded that the system was successfully created using the PHP programming language by implementing the AHP and Promethee methods, so the best suggestions are obtained with the results of calculations on the system same as manual calculations that have been previously calculated.